An assessment of hydrocarbon species in the methanol-to-hydrocarbon reaction over a ZSM-5 catalyst. (14th February 2017) - Suwardiyanto,; Howe, Russell F.; Gibson, Emma K.; Catlow, C. Richard A.; Hameed, Ali; McGregor, James; Collier, Paul; Parker, Stewart F.; Lennon, David
Abstract : A ZSM-5 catalyst is examined in relation to the methanol-to-hydrocarbon (MTH) reaction as a function of reaction temperature and time-on-stream. The reaction profile is characterised using in-line mass spectrometry. Furthermore, the material contained within a catch-pot downstream from the reactor is analysed using gas chromatography-mass spectrometry. For a fixed methanol feed, reaction conditions are selected to define various stages of the reaction coordinate: (i) initial methanol adsorption at a sub-optimum reaction temperature (1 h at 200 °C); (ii) initial stages of reaction at an optimised reaction temperature (1 h at 350 °C); (iii) steady-state operation at an optimised reaction temperature (3 days at 350 °C); and (iv) accelerated ageing (3 days at 400 °C). Post-reaction, the catalyst samples are analysed ex situ by a combination of temperature-programmed oxidation (TPO) and spectroscopically by electron paramagnetic resonance (EPR), diffuse-reflectance infrared and inelastic neutron scattering (INS) spectroscopies. The TPO measurements provide an indication of the degree of 'coking' experienced by each sample. The EPR measurements detect aromatic radical cations. The IR and INS measurements reveal the presence of retained hydrocarbonaceous species, the nature of which are discussed in terms of the well-developed 'hydrocarbon pool' mechanism. This combination of experimental evidence, uniquely applied to this reaction system, establishes the importance of retained hydrocarbonaceous species in effecting the product distribution of this economically relevant reaction system.